2016
DOI: 10.1073/pnas.1516953113
|View full text |Cite
|
Sign up to set email alerts
|

Circadian misalignment increases cardiovascular disease risk factors in humans

Abstract: Shift work is a risk factor for hypertension, inflammation, and cardiovascular disease. This increased risk cannot be fully explained by classic risk factors. One of the key features of shift workers is that their behavioral and environmental cycles are typically misaligned relative to their endogenous circadian system. However, there is little information on the impact of acute circadian misalignment on cardiovascular disease risk in humans. Here we show-by using two 8-d laboratory protocols-that short-term c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
343
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(384 citation statements)
references
References 80 publications
12
343
2
8
Order By: Relevance
“…Due to its retrospective design, the study does not include potentially confounding variables such as shift work, which is considered a risk factor for hypertension, insulin resistance, obesity, and dyslipidaemia. [35][36][37] It has been suggested that shift work may cause a rise in BP or cause progression of hypertension [38][39][40][41][42] ; however, this is not supported by more recent studies. [43][44][45] Nevertheless, not including shift work as a confounding factor may be considered as a limitation and we recognize the need for controlling for shift work in future research on the subject.…”
mentioning
(Expert classified)
“…Due to its retrospective design, the study does not include potentially confounding variables such as shift work, which is considered a risk factor for hypertension, insulin resistance, obesity, and dyslipidaemia. [35][36][37] It has been suggested that shift work may cause a rise in BP or cause progression of hypertension [38][39][40][41][42] ; however, this is not supported by more recent studies. [43][44][45] Nevertheless, not including shift work as a confounding factor may be considered as a limitation and we recognize the need for controlling for shift work in future research on the subject.…”
mentioning
(Expert classified)
“…Improved understanding of the distinction between these concepts may create valuable opportunities to intervene and improve quality of life. This is particularly important in light of mounting evidence that disrupted circadian rhythms are an early warning sign of developing neurodegenerative diseases, such as Alzheimer's, Parkinson's, and Huntington's (3)(4)(5), and that the circadian clock is heavily implicated in the etiology of metabolic diseases, chronic inflammation, and cancers (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance of circadian rhythms due to, for example, shift-work (Kecklund and Axelsson 2016), circadian disorders or dysregulation of rhythmicity (McHill and Wright 2017;Morris et al 2016;Kadono et al 2016;Gamaldo et al 2014;Dickerman et al 2016) increase the morbidity risk of cardiovascular disease (Reutrakul and Knutson 2015), metabolic disease (Arble et al 2010) and cancers (Levi and Schibler 2007). Recent work has shown that disruption of the circadian clock leads to dysregulation of immune responses which underlie the pathophysiological basis of disease, suggesting an important regulatory role of the circadian system.…”
Section: Introductionmentioning
confidence: 99%